Abstracts of the 22nd International Isotope Society (UK Group) Symposium: synthesis and applications of labelled compounds 2013. (26th January 2014) - Aboagye, E. O.; Aigbirhio, F. I.; Allen, P.; Arent, R.; Arrowsmith, R. L.; Banci, G.; Bagley, M. C.; Bailey, C. D.; Blake, T.; Bunt, A. J.; Bushby, N.; Carroll, L.; et al.
<x xml:space="preserve">Abstract</x> Meeting Summary The 22nd annual symposium of the International Isotope Society's United Kingdom Group took place at the Møller Centre, Churchill College, Cambridge, UK, on Friday, 18 October 2013. The meeting was attended by 65 delegates from academia and industry; the life sciences; and chemical, radiochemical and scientific instrument suppliers. Delegates were welcomed by Dr Ken Lawrie (GlaxoSmithKline, UK, chair of the IIS UK group). The subsequent scientific programme consisted of oral and poster presentations on isotopic chemistry and applications of labelled compounds, or of chemistry with potential implications for isotopic synthesis. Both short‐lived and long‐lived isotopes were represented, as were stable isotopes. The symposium programme was divided into a morning session chaired by Dr Karl Cable (GlaxoSmithKline, UK) and afternoon sessions chaired by Mr Mike Chappelle (Quotient Biosciences, UK) and by Dr Nick Bushby (AstraZeneca, UK). The UK meeting concluded with remarks from Dr Ken Lawrie (GlaxoSmithKline, UK).